2007
DOI: 10.1007/s10350-006-0827-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Translocation May Influence the Long-Term Survival in Colorectal Cancer Patients

Abstract: Colorectal cancer patients with bacterial translocation in the mesenteric lymph nodes have a worse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
(21 reference statements)
0
22
0
1
Order By: Relevance
“…39, 40 Since the liver is the first organ receiving blood from the intestines, bacterial components may activate KCs and PMNs and induce ROS production. Patients with positive bacterial translocation after surgery had significantly shorter disease-free survival, 41 supporting the negative impact of bacterial contamination after surgery on oncological outcome. However, the exact role of bacterial translocation in liver metastases development is unknown.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…39, 40 Since the liver is the first organ receiving blood from the intestines, bacterial components may activate KCs and PMNs and induce ROS production. Patients with positive bacterial translocation after surgery had significantly shorter disease-free survival, 41 supporting the negative impact of bacterial contamination after surgery on oncological outcome. However, the exact role of bacterial translocation in liver metastases development is unknown.…”
Section: Introductionmentioning
confidence: 81%
“…51, 52 Importantly, a recent study demonstrated that bowel mobilization already led to bacterial translocation in patients. 40 Furthermore, patients with anastomotic leakage or who encountered bacterial translocation after a colectomy had poor disease-free survival, 41 indicating that bacterial contamination had a negative impact on long-term patient outcome. Even though this simplified surgical rat model does not completely reflect the human situation, as multiple peri- and post-operative factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, six additional clinical series totaling 2125 patients undergoing abdominal surgery have shown that the incidence of bacterial translocation ranges from 5% to 21% and that in each of these studies, bacterial translocation was associated with a significant twofold to threefold increase in the rate of septic complications. [15][16][17][18][19][20] Furthermore, in about half of these patients, the same organism was identified in the mesenteric lymph nodes as in the postoperative septic focus. [15][16][17][18][19][20] The notion that the gut was the reservoir for these translocating bacteria has been strengthened further by genomic studies showing that the bacteria in the mesenteric lymph nodes originated from the patients, gut flora.…”
Section: Gut-derived Sepsis: Do They Exist?mentioning
confidence: 92%
“…[15][16][17][18][19][20] Furthermore, in about half of these patients, the same organism was identified in the mesenteric lymph nodes as in the postoperative septic focus. [15][16][17][18][19][20] The notion that the gut was the reservoir for these translocating bacteria has been strengthened further by genomic studies showing that the bacteria in the mesenteric lymph nodes originated from the patients, gut flora. 21 Thus, several studies of patients undergoing laparotomy have validated the concept that bacterial translocation occurs and that bacterial translocation is associated with a significantly higher incidence of systemic infectious complications in patients undergoing abdominal surgery.…”
Section: Gut-derived Sepsis: Do They Exist?mentioning
confidence: 92%
See 1 more Smart Citation